Circulating Angiopoietin-2 Is a Marker for Early Cardiovascular Disease in Children on Chronic Dialysis - Shroff, Rukshana C. (Public Library of Science, 2013)
Cardiovascular disease (CVD) is increasingly recognised as a complication of childhood chronic kidney disease (CKD) even in the absence of diabetes and hypertension. We hypothesized that an alteration in angiopoietin-1 and -2, growth factors which regulate endothelial and vascular function could be involved. We report that the endothelial survival factor, angiopoietin-1 is low in children with pre-dialysis CKD whereas the pro-inflammatory angiopoietin-2 is elevated in children on dialysis. In dialysis patients, angiopoietin-2 positively correlated with time on dialysis, systolic blood pressure, and carotid artery intima media thickness. Elevated angiopoietin-2 levels in dialysis versus pre-dialysis CKD patients were also associated with an anti-angiogenic (high soluble VEGFR-1 and low VEGF-A) and pro-inflammatory (high urate, E-selectin, P-selectin and VCAM-1) milieu. Ang-2 was immunodetected in arterial biopsy samples whilst the expression of VEGF-A was significantly downregulated in dialysis patients. Serum urate correlated with angiopoietin-2 levels in dialysis patients and addition of uric acid was able to induce rapid release of angiopoietin-2 from cultured endothelial cells. Thus, angiopoietin-2 is a marker for cardiovascular disease in children on chronic dialysis and may act as an anti-angiogenic and pro-inflammatory effector in this context. The possibility that the release of angiopoietin-2 from endothelia is mediated by urate should be explored further.